FOREIGN EXCHANGE ACCOUNTING. - Saliers, E. A. (The Accounting Review, 1944)
Abstract A study of authorities in the U.S. and Great Britain leaves much to be desired as regards the exact procedure to be followed in incorporating the results of foreign branch transactions on the books of the home office. It is evident that several variants in procedure are possible. The simplest arrangement for recording branch and home office relationships is the use of one account current in each record The home office Branch Current account will show in domestic currency the amount of the home office investment in the branch and the Home Office Current account in the branch ledger will show the home office proprietorship or residual liability of the branch to the home office stated in foreign currency. The credit balance in the Home Office Current account represents net assets whose various debit balances may have arisen under various exchange conditions and been converted into terms of domestic currency at various rates. Substitution of the balance of the Branch Current account for the balance of the Home Office Current account would be easier and more effective than conversion of the balance of the latter account.